Electrospun nanofibres and their applications - He, Ji-Huan (ISmithers, 2008)
This Update covers all aspects of electrospinning as used to produce Nanofibres. It contains an array of colour diagrams, mathematical models, equations and detailed references. Electrospinning is the cheapest and the most straightforward way to produce nanomaterials. Electrospun Nanofibres are very important for the scientific and economic revival of developing countries. It is now possible to produce a low-cost, high-value, high-strength fibre from a biodegradable and renewable waste product for easing environmental concerns. For example, electrospun nanofibres can be used in wound dressings.